Internalization of Islamic Education Values in the Formation of Santri Entrepreneur at Islamic Boarding School in Lampung - Sarohmad Sarohmad; Ahmad Zumaro (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to analyze the process of internalizing Islamic education values in the formation of santri entrepreneur at Islamic boarding school in Lampung, as well as to identify the supporting and inhibiting factors. The study employed a qualitative approach with a descriptive type through observation, interviews, and documentation. The findings indicate that value internalization occurs systematically through three main stages: value transformation through the teaching of aqidah, akhlak, and fiqh muamalah; habituation and role modeling in boarding school life, and the actualization of values through entrepreneurial practices in the boarding school's business units. Values such as honesty, trustworthiness, responsibility, hard work, and independence are integrated into economic activities, thereby shaping santri with religious character and social orientation. The main supporting factors include visionary kyai leadership, a disciplined Islamic Boarding School culture, the presence of business units as practical laboratories, and the support of alumni and community networks. Meanwhile, inhibiting factors include limited capital and production facilities, business management that is not yet fully professional, limited digital literacy, and differences in santri interests and talents. Overall, this study concludes that the model of internalizing Islamic Education values in the Islamic boarding school is effective in forming santri entrepreneurs who are not only economically competent, but also possess moral integrity and social responsibility. This model has the potential to serve as an alternative for developing value-based Islamic entrepreneurship education in the context of empowering the economic well-being of the ummah.